Pelatihan Dasar Pembuatan Merek Sebagai Identitas Produk UMKM Kelurahan Argasari - Rendy Sudirman; Heru Kurniawan; Ferryan Nugraha (Jurnal Pengabdian Manajemen, 2023)
Brands can be the strength of a product that is trusted by consumers. Micro, Small, and Medium Enterprises in Argasari Village, Cihideung District, Tasikmalaya City Basic Brand Making Training as a product identity has had an impact on Argasari Village business actors, totaling 28 people, as evidenced by the increase in the category of "less" knowledge during the pre-test by 35.71% to 3.57%, "enough" from 57.14 percent to 42.86%, and the "good" category from 7.14% to 53.57%. The significance of the training results can provide advantages in increasing the sales volume of MSME products.